Analysis Types Figurative Language in Maya Angelou's Poems - lestari, Mimin Ayu; Sogimin, Sogimin (Universitas 17 Agustus 1945 Semarang, 2024)
The use of figurative language adds to the unique of the literature, which can create an imaginative atmosphere for the reader. The analysis is about type’s figurative language of in Maya Angelou's. There are three poems the writer uses in thesis. The research method of this thesis is descriptive qualitative using a descriptive approach. The purpose of this analysis is to find figurative language in Maya Angelou's poem. The selected poems are